2019
DOI: 10.1016/j.atherosclerosis.2019.06.714
|View full text |Cite
|
Sign up to set email alerts
|

Non-Cholesterol Sterol Concentrations As Biomarkers For Cholesterol Absorption And Synthesis In Different Metabolic Disorders: A Systematic Review

Abstract: Non-cholesterol sterols are validated biomarkers for intestinal cholesterol absorption and endogenous cholesterol synthesis. However, their use in metabolic disturbances has not been systematically explored. Therefore, we conducted a systematic review to provide an overview of non-cholesterol sterols as markers for cholesterol metabolism in different metabolic disorders. Potentially relevant studies were retrieved by a systematic search of three databases in July 2018 and ninety-four human studies were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 29 publications
(37 reference statements)
2
15
1
1
Order By: Relevance
“…Previous studies have demonstrated that beta-sitosterol has been widely used in the treatment of proteinuria resulting from diabetes and kidney disease [63][64][65]. Berberine has also been reported to treat proteinuria and kidney damage caused by diabetes and hypertension [66][67][68], which provided evidence for our results.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have demonstrated that beta-sitosterol has been widely used in the treatment of proteinuria resulting from diabetes and kidney disease [63][64][65]. Berberine has also been reported to treat proteinuria and kidney damage caused by diabetes and hypertension [66][67][68], which provided evidence for our results.…”
Section: Discussionsupporting
confidence: 79%
“…Our data contribute to explain investigation in cases of metabolic syndrome in which decreased intestinal absorption of cholesterol is associated with lower efficiency of PS esters in reducing blood cholesterol although the cholesterol synthesis markers had not been measured [31]. Such a result may be consequent to elevated cholesterol synthesis in cases of metabolic syndrome [16]. In summary, responders absorbed more PS than non-responders likely resulting from responders delivering less endogenous cholesterol into the intestinal lumen that facilitates greater absorption of PS by the intestine.…”
Section: Discussionmentioning
confidence: 82%
“…Plasma concentrations of PS, and of non-cholesterol sterol precursors of cholesterol synthesis, respectively, markers of the intestinal cholesterol absorption and of the body's cholesterol synthesis have been utilized as markers of atherosclerotic cardiovascular disease [12] [13] [14] [15] [16] [17].…”
Section: Introductionmentioning
confidence: 99%
“…An important limitation of the present study is the use of serum markers of cholesterol synthesis and absorption rather than isotope tracer measurements which directly assess cholesterol synthesis and absorption 32‐34 . However, such direct measurements are not practical in a cohort of this size and serum markers of synthesis and absorption correlate well with direct measurements 35‐39 …”
Section: Discussionmentioning
confidence: 99%